Domain-Specific Hardware Accelerators: DSAs gain efficiency from specialization and performance from parallelism. - DALLY, WILLIAM J.; TURAKHIA, YATISH; SONG HAN (Communications of the ACM, 2020)
The article discusses hardware computing engines known as domain-specific accelerators (DSAs). It discusses Moore's Law, the design of the DSA, and various sources of acceleration for DSAs. It also discusses algorithms, total cost of ownership (TCO), and memory in the accelerators.